Challenges of COVID: Lessons Learned From Living Kidney Donors’ Experience - Kelly L. Nottingham PhD, MPH; Rebekah Perkins Crawford PhD; Sophia D. Starkie BSH; Libby K. Shaffer (Journal of Patient Experience, 2025)
The COVID pandemic disrupted healthcare systems worldwide, affecting medical care delivery, including transplant centers. As sites of tertiary healthcare delivery, living kidney donations were particularly impacted, with delays, communication challenges, and an increased burden on potential donors. This qualitative study explored the lived experiences of individuals navigating the predonation evaluation (PDE) during the pandemic. Through 25 semistructured interviews, the participants shared insights into delays in care, inconsistent communication, pandemic-related emotions, and unexpected facilitators. The constant comparative analysis method identified key themes, including (1) delays in care due to COVID, (2) inconsistent communication due to COVID, (3) pandemic-related emotions, and (4) pandemic-era shifts that facilitated living kidney donor (LKD) PDE. The data highlighted the importance of maintaining patient-centered care, effective communication and pointed to specific ways to improve the patient's experience. These themes highlight mitigating strategies to address future care for other types of LKD disruptions.